Complex treatment approach to primary open-angle glaucoma: focus on neuroprotection - M. Kh. Khubetsova; V.V. Kadyshev; B.F. Ambalova (РМЖ "Клиническая офтальмология")
M. Kh. Khubetsova1, V.V. Kadyshev2, B.F. Ambalova3 1S.N. Fedorov NMRC “MNTK “Eye Microsurgery”, Moscow, Russian Federation 2Moscow Genetic Research Center, Moscow, Russian Federation 3Right-Shore Central Regional Clinical Hospital, Beslan, Russian Federation According to the WHO, glaucoma is now the second leading cause of blindness globally. It was demonstrated that effective treatment for glaucoma should include both IOP reduction and neuroprotection. However, even pathogenic treatment for glaucoma can be ineffective due to the poor adherence to treatment. Currently, treatment compliance is of great importance. Ocular surface disorders inevitably resulting from long-term instillations of IOP-lowering medications are among the factors affecting medication non-adherence. Tear replacement therapy is a potential solution which, however, increases the number of medications and instillations and results in poor medication adherence. Brimonidine tartrate 0.2% provides both IOP-lowering and neuroprotective effects while polyvinyl alcohol moisturize and protects ocular surface. Polyvinyl alcohol improves dry eye symptoms in long-term therapy when adding brimonidine to glaucoma treatment. Keywords: glaucoma, intraocular pressure, neuroprotection, ocular surface, compliance, brimonidine, Luxfen. For citation: Khubetsova M.Kh., Kadyshev V.V., Ambalova B.F. Complex treatment approach to primary open-angle glaucoma: focus on neuroprotection. Russian Journal of Clinical Ophthalmology. 2019;19(4):224–228.